Predicted Interactionsof Cyclooxygenase2 with Nasopharyngeal Cancer-linked Ribosomal Proteins, uS19 and eL27 - Alyaa Syafiqah, Shamsuri; Sim, Edmund Ui Hang (Radiance Research Academy, 2022)
Introduction: The Cyclooxygenase 2 (COX-2) and ribosomal proteins (RP) of uS19 and eL27 were reported to be associated with nasopharyngeal cancer (NPC). However, there is no studies on their interactions. Objective/Aim: This study aimed to extrapolated the interactions of COX-2 with uS19 and eL27 via in silico approach. Methods: Bioinformatics analysis involving the web-based applications of SWISS-MODEL, ClusPro, FireDock/PatchDock and Protein Interaction Calculator (PIC), and the UniProfKB database were used for the purpose of our study. Results: We revealed possible interactions between uS19 and eL27 with COX-2 individually. Evaluation of the interacting interface amino acid residues of the uS19-COX2 and eL27-COX2 complexes show hydrophobic and ionic bonds in the former and only hydrophobic bonds in the latter. Conclusion: Our findings provide novel in silico evidence of COX-2’s interactions with two NPC-associated RPs (uS19 and eL27), and propose an interplay among these proteins during the oncogenesis of NPC.